Nutritional Evaluation Of Organically And Conventionally Grown Kale (Brassica Oleraceae L. Var. Acephala) (Applied Biological Research, 2018)
In present study various physicochemical constituents of organically and  conventionally grown kale (Brassica oleraceae L. var. acephala) were studied.  The proximate constituents were determined by standard methods. The  results revealed that dry matter, crude protein, crude fat, ash and total  carbohydrate content in organically and conventionally grown kale were  12.15, 3.54, 0.68, 2.11 and 6.09 and 10.60, 2.66, 0.53, 1.63 and 5.78%,  respectively. The total sugars, reducing sugar and ascorbic acid contents in  organically grown kale were 1.95%, 1.05%, 49.0 mg 100 g-1 as compared to  1.87%, 1.02% and 44.0 mg 100 g-1, respectively, in conventionally grown kale.  The sodium and potassium contents were high in organically grown kale. Kale  grown with organic inputs was found nutritionally superior to conventionally  grown kale so can be incorporated in food formulation as therapeutic agent.
Keywords: Conventional cultivation; kale; nutritional value; organic